Sweden : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2003)
This Selected Issues paper analyzes the strengths and weaknesses of the fiscal framework of Sweden, and discusses some guidelines for their modification. It describes the Swedish experience under the new fiscal framework, and documents the increasing expenditure profile during the economic boom. It describes the basic rationale for fiscal rules, different types of fiscal rules, and also provides suggestions for improving the framework.